2017
DOI: 10.1177/2470547017715645
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress in Adolescents and Its Neurobiological and Psychopathological Consequences: An RDoC Perspective

Abstract: The Research Domain Criteria (RDoC) initiative provides a strategy for classifying psychopathology based on behavioral dimensions and neurobiological measures. Neurodevelopment is an orthogonal dimension in the current RDoC framework; however, it has not yet been fully incorporated into the RDoC approach. A combination of both a neurodevelopmental and RDoC approach offers a multidimensional perspective for understanding the emergence of psychopathology during development. Environmental influence (e.g., stress)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 252 publications
(304 reference statements)
0
78
0
3
Order By: Relevance
“…In addition, antidepressants – known to reverse the CSP in animals – have shown efficacy in alleviating symptoms of PTSD, GAD, OCD, bipolar depression, and other disorders with a considerable chronic stress component. Here, we note that synaptic dysconnectivity could be a predisposing factor, an outcome, or a perpetuator of the psychopathology (Averill, Purohit, et al, 2017; Matosin, Cruceanu, & Binder, 2017; Sheth, McGlade, & Yurgelun-Todd, 2017; Syed & Nemeroff, 2017). Furthermore, while synaptic loss appears to be common across stress-related disorders, the location and pattern of the synaptic dysconnectivity, combined with individual characteristics (e.g., genes & environment), may be the mechanism through which CSP is associated with distinct clinical presentations and psychopathologies (Abdallah, Southwick, & Krystal, 2017; Averill, Purohit, et al, 2017; Krystal, et al, 2017).…”
Section: Synaptic Model Of Chronic Stress Pathology (Csp)mentioning
confidence: 92%
“…In addition, antidepressants – known to reverse the CSP in animals – have shown efficacy in alleviating symptoms of PTSD, GAD, OCD, bipolar depression, and other disorders with a considerable chronic stress component. Here, we note that synaptic dysconnectivity could be a predisposing factor, an outcome, or a perpetuator of the psychopathology (Averill, Purohit, et al, 2017; Matosin, Cruceanu, & Binder, 2017; Sheth, McGlade, & Yurgelun-Todd, 2017; Syed & Nemeroff, 2017). Furthermore, while synaptic loss appears to be common across stress-related disorders, the location and pattern of the synaptic dysconnectivity, combined with individual characteristics (e.g., genes & environment), may be the mechanism through which CSP is associated with distinct clinical presentations and psychopathologies (Abdallah, Southwick, & Krystal, 2017; Averill, Purohit, et al, 2017; Krystal, et al, 2017).…”
Section: Synaptic Model Of Chronic Stress Pathology (Csp)mentioning
confidence: 92%
“…2, and asiaticoside (3) (major active components of C. asiatica), quercetin (4), kaempferol (5), kaempferol-3-glucoside (6), rutin 7, luteolin-7-O-glucoside (8), ferulic acid (9) (major constituents of N. nucifera) were used as markers in the HPLC analysis of the KBD extract ( Figure 5). Six different concentrations of standard solutions, i.e., 5-100 µg/mL for piperine (1), 5-30 µg/mL for madecassoside (2) and asiaticoside (3), 1-6 µg/mL for ferulic acid (9), luteolin-7-O-glucoside (8), rutin 7, kaempferol-3-glucoside (6), quercetin (4), and kaempferol (5), were used. This HPLC method for the analysis of these compounds was accurate and reliable, as demonstrated by the validation results.…”
Section: Total Phenolic and Flavonoid Contentsmentioning
confidence: 99%
“…Accumulated evidences demonstrated that chronic stress negatively affects neural plasticity and neurogenesis which produce depressive symptom, impairment in memory and learning processes [1,2]. The deleterious effect of chronic stress is modulated by the stress hormone, cortisol/corticosterone (CORT), neurotrophins, and various neurotransmitters [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest, structural alteration (e.g., volumetric changes) in subcortical regions including the amygdala, hippocampus, and NAcc has been known to be associated with both social stress and psychopathology 9,10 . This may be because these regions have been implicated in social and emotion processing and reward-punishment processing 11,12 . These regions are also known to be sensitive to social stress 13 , and continue to develop throughout the adolescence 14 .…”
mentioning
confidence: 99%